What Intellectual Ethics for Contemporary Science? Perspectives of Virtue Epistemology - Jarczewski, Dominik (Ruch Filozoficzny, 2022)
In face of unethical incidents that threaten the world of science, a question of the necessity and a possible shape of intellectual ethics has been raised. The article argues that advantages of virtue epistemology make it more attractive than other models of intellectual ethics (deontology, in particular). To that purpose, it reviews alternative models for intellectual ethics, analyses and criticises deontological approach and demonstrates the virtues of the virtue approach. As problems with implementation of virtue ethics have been put against that approach, the article addresses the question of how to promote virtue intellectual ethics. It discusses four possible methods of formation in virtues: theoretical, success-oriented, social and based on emulating exemplars. It argues for the role of excellent exemplars (both direct and narrative) whose emulation forms virtues in agent. The conclusions of the article should transform the way we think about intellectual ethics and promote it.